Effects of pellet fertilizer prepared from Azolla and zinc oxide nanoparticles on rice growth and yield - Theerak, Winakon; Atiganyanun, Sarun; Tharawetcharak, Pattrawet; Pimonrat, Pimpan; Tokhun, Natsima (Agriculture and Natural Resources, 2026)
Importance of the work: The combination of zinc oxide nanoparticles (nZnO) and Azolla as fertilizer could reduce chemical fertilizer use and alleviate zinc deficiency. Objectives: To evaluate the impact of pellet fertilizers containing nZnO and dried Azolla on Pathum Thani 1 rice growth and yield. Materials and Methods: A one-factor completely randomized design was used. The weight contents of Azolla and nZnO in pellet fertilizer were 60.96% and 0.04%, 60.92% and 0.08% and 60.88% and 0.12%, respectively. The performance was evaluated of the different pellet fertilizers on rice growth, yield and yield components and on the concentration of zinc in plant organs. Results: The pellet fertilizer significantly improved the SPAD index of Pathum Thani 1 rice, compared to the control. This improvement was not significantly different from the use of urea fertilizer. Similar to urea fertilizer, the pellet fertilizer significantly enhanced plant height, the number of tillers per hill, the number of panicles and the number of grains per panicle. However, the treatments did not significantly affect the weight of paddy and brown rice. The inclusion of nZnO led to a significant increase in zinc accumulation in the rice roots, leaves and grains. There was greater zinc accumulation in the treatments with increasing nZnO dosages. Main finding: The Azolla-nZnO pellet fertilizer effectively improved rice growth and increased the zinc content in grains. This eco-friendly pellet fertilizer could be used to improve zinc nutrition in rice-consuming regions. Further study is required to improve its performance in promoting grain weight.